Stable Matching Algorithm for an Agile Reconfigurable Data Center Interconnect - Devanur, Nikhil; Kulkarni, Janardhan; Ranade, Gireeja; Ghobadi, Manya; Mahajan, Ratul; Phanishayee, Amar (MSR Technical Report, 2016)
This document describes the scheduling algorithm used in the ProjecToR data-center interconnect system. The algorithm assigns bundles to laser-photodetector edges as they arrive online with the goal of minimizing the bundle/flow completion times over all bundles in the system. We compare the performance of the proposed stable-matching algorithm to the optimal performance of a more powerful hindsight optimal algorithm that is aware of all the bundles arriving in the system and can operate offline. We also give an integer linear programming formulation for the problem of maximizing instantaneous throughput.